Electrically driven three-dimensional solitary waves as director bullets in nematic liquid crystals - Bing-Xiang Li (Nature Portfolio, 2018)
Solitary waves which maintain their shape have many fascinating physical and mathematical properties. Here the authors observe waves trapped along three spatial dimensions in nematic liquid crystals due to an electric field and show that these director bullets can re-form after collisions.